Differences in morphological properties between the olivine group minerals formed in natural and industrial processes - Dević S.; Marčeta L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Olivines are a large isomorphic series of minerals, belonging to silicates group. Regardless of their chemical composition, any of these minerals can be formed both in natural and industrial processes. The aim of this work is to describe these minerals and differences of morphological properties between the olivines formed in nature, and those formed as byproducts of some industrial processes , as Process Metalurgy-Ironmaking. The olivines whose formation is tied to rock masses (natural process) and the olivines genetically tied to industrial processes of black metallurgy slags (process metallurgy-Ironmaking) are shown in this paper. The morphological properties of these minerals and their differences have been analyzed by optical microscopy in refracted and in reflected light. .